Correction: Offshore Habitat Preference of Overwintering Juvenile and Adult Black Sea Bass, Centropristis striata, and the Relationship to Year-Class Success. - Alicia S Miller; Gary R Shepherd; Paula S Fratantoni (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0147627.].